Pelatihan Interview Etiquette sebagai Persiapan Mencari Pekerjaan Siswa SMK Widjaya (Yayasan Pendidikan Widjaya) Ngoro Jombang - Rizka Maulina Wulandari; Moh. Farid Maftuh; Jannatul Laily Noviabahari; Anggi Arlendo (Lembaga Pengembangan Kinerja Dosen, 2024)
Understanding professional ethics in the workplace is a crucial aspect for students in Vocational High Schools (SMK) to prepare themselves for entering the workforce. This ethics is not only related to technical skills but also encompasses attitudes, behavior, and the ability to interact professionally. One of the most critical aspects is interview etiquette, as a student’s success is often determined by how they behave and communicate during the interview. An interview is not just about answering questions, but also an opportunity to present a positive self-image. Therefore, students need to understand how to use appropriate body language, manage facial expressions, and answer questions confidently. To address this need, the community service team from the D-III English Language Study Program at Politeknik Negeri Madiun conducted an interview etiquette training at SMK Widjaya Ngoro, Jombang. The training was delivered through interactive discussions and hands-on practice. In the discussion session, students learned preparation strategies, interview etiquette, and follow-up actions after the interview. Furthermore, through simulations, students were able to practice communication skills, improve their attitudes, and build confidence. This activity proved to be beneficial as it enriched knowledge and provided practical experience that is relevant for facing job selection processes in the future.